River of Change: a Model for the Development of Terraces Along the Bow River, Alberta - Oetelaar, Gerald (Géographie physique et Quaternaire, 2002)
AbstractResearchers working in the Bow River valley have identified a minimum of four alluvial terraces, the upper two of which have been designated as paired terraces. Over the past 35 years, they have attempted to correlate these alluvial landforms and to generate models for the development of the terraces along the section of the Bow River between Calgary and the Rocky Mountains. In this study, Mazama ash and an early Holocene paleosol are used to correlate the terrace suites examined by previous researchers and to generate a model which accounts for the development of the upper two sets of paired terraces. These paired terraces reflect major episodes of aggradation and degradation that result from changes in independent variables such as climate and uplift. The initial episode of aggradation, dating from the late Pleistocene, is the result of paraglacial processes in a sparsely vegetated, yet saturated environment. Following a brief episode of degradation at the end of the Younger Dryas, the second episode of aggradation, dating from 9000 to 5000 BP, is caused by increased sediment load and lowered stream power during the Hypsithermal.